[OP.5C.06] MASKED TACHYCARDIA PREDICTS ADVERSE OUTCOME IN HYPERTENSION. THE ABP-INTERNATIONAL STUDY. (September 2016) - Palatini, P.; Reboldi, P.; Pierdomenico, S.; Eguchi, K.; Kario, K.; Imai, Y.; Ohkubo, T.; Beilin, L.; Wing, L.; Schwartz, J.; Casiglia, E.; Verdecchia, P.
Abstract : Objective: Heart rate (HR) is a well known predictor of cardiovascular events (CVE) and mortality but the relative role of resting office HR and ambulatory HR for predicting these outcomes is not well known. Aim of this study was to investigate the association of white-coat tachycardia and masked tachycardia with CVE and all-cause mortality in hypertensive subjects. Design and method: We performed 24-hour ambulatory blood pressure and HR monitoring in 7602 hypertensive patients (4165 men) aged 52 ± 16 years enrolled in 8 prospective studies in Italy, U.S.A., Japan, and Australia. None of the participants had atrial fibrillation and all were untreated at baseline examination. Office and ambulatory tachycardia were defined according to previously published criteria (J Hypertens 2014;32:2099). Participants were divided into 4 groups: 1) normal office and normal ambulatory HRs (N = 5238), 2) white-coat tachycardia (high office and normal ambulatory HR, N = 998), 3) masked tachycardia (normal office and high ambulatory HR, N = 796), and 4) sustained tachycardia (N = 570). Results: During a median follow-up of 5.0 years the rates of fatal plus nonfatal CVE and of all-cause mortality were 8.4% and 3.7%, respectively. In an age-and-sex-adjusted Cox model, using the normal HRs group as a reference, white-coat tachycardia was not a significant predictor of outcome. In contrast, both masked tachycardia (hazard ratio, 95% CI; 1.36, 1.07–1.72) and sustained tachycardia (1.94, 1.51–2.49) were associated with risk of CVE. In addition, masked tachycardia (hazard ratio, 95% CI; 1.59, 1.12–2.25) but not sustained tachycardia (1.22, 0.75–1.98) was a significant predictor of mortality. These relationships held true in multivariable parsimonious Cox models in which sex, age, diabetes, smoking, creatinine, total cholesterol, and ambulatory blood pressure were included. In these models, masked tachycardia remained an independent predictor of CVE (hazard ratio, 95% CI; 1.34, 1.06–1.71) and all-cause mortality (1.68, 1.17–2.43). Conclusions: This study confirms that measurement of HR adds to the risk stratification for CVE and mortality and shows that an elevated ambulatory HR confers an increased cardiovascular risk to hypertensive patients also in the presence of a normal office HR.